Letters of Maria Kuncewiczowa to Her Late Husband - Wzorek, Anna (Respectus Philologicus, 2017)
The article discusses the last book of Maria Kuncewiczowa – a set of twenty-three letters (provided with a postscript) addressed to her deceased husband. The uniqueness of this correspondence, presented in literary form, lies in the fact that the recipient is dead, treated by the sender as someone constantly present in the real world and still associated with the temporality. Listy do Jerzego (Letters to Jerzy) are – as Tadeusz Swat, one of the reviewers say – “an attempt at denial of death, to save Jerzy by love, memory, and literature.”The analysis of the work highlights the occurring axiological categories. It has been demonstrated that Letters to Jerzy is a book about eternal love reaching beyond the grave (in this respect, in stark contrast with Tristan 1946), felt with dignity of old age, and finally transcending into faith. Letters to Jerzy is also an attempt to reduce the suffering of the writer over the loss of her beloved husband. To some extent, therefore, they correspond to her earlier work Cudzoziemka (Foreigner) in which Kuncewiczowa liberates from the negative emotions associated with the death of her mother.
Keywords: contemporary literature; funeral literature; novel of letters; Maria Kuncewiczowa and Jerzy Kuncewicz